Exploring embodiment in drama therapy for enhancing intercultural communication - Annandale, Amari (My University, 2017)
This qualitative research study examines the ways in which embodiment in drama therapy can be an effective intervention aimed at enhancing intercultural communication amongst South Africans. South Africa is a multicultural society owing to the diverse cultures people belong to. Communication is required in order for multiculturalism to succeed and peaceful coexistence to be stimulated. This study involved six participants who engaged in a series of six drama therapeutic group sessions focused on embodiment. Using interpretative phenomenological analysis the study found that the participants were able to enhance the intercultural communication amongst them as well as develop cross-cultural relationships. This research report consists of an exploration of the South African context. Thereafter embodiment, culture and communication are discussed to understand how these aspects influence the participants and their daily lives. Chapter three is the exploration of both globalisation and intercultural communication. Chapter four gives an explication of embodiment as a drama therapy approach and what embodiment offers the individual, followed by chapter five which demonstrates the methodology applied to investigate the method of embodiment. The main chapter of this study is chapter six and discusses the embodied drama therapy process and how it became a comfort zone for the participants in which they could communicate and develop meaningful relationships with the fellow participants. Chapter seven concludes and discusses the limitations and recommendations for the research. The drama therapy methodologies empowered participants and enabled them to think about themselves, their behaviour and how they communicate in a different way. It further enabled unconscious material to surface to the conscious mind, thereby evoking introspection and reflection.
A research report submitted to the Wits School of Arts in partial fulfilment of the requirements for the degree of Masters of Arts by coursework and research report in the field of Drama Therapy, in the faculty of Humanities, University of the Witwatersrand, Johannesburg. March 2017
Keywords: Drama--Therapeutic use--South Africa; Drama--Psychological aspects; Intercultural communication--South Africa